Role of online supportive environment in professional development of in-service teachers : Case of TELMAE - Lustigova, Zdena (2006)
The paper provides a structured overview drawing on the results of the first four years of a country-wide activity focused on professional development of science teachers. This activity, organized by the Laboratory of Distance Education, Charles University in Prague within the framework of the State Information Policy (SIP) in Education Program, started in 2001, and it has become one of the top online learning activities in the country. The paper introduces the whole developed system of in-service teacher training on a “voluntary basis” and focuses on the TELMAE Science Teachers’ Online Supportive Environment, developed also at the Laboratory of Distance Education at Charles University. The TELMAE supportive environment incorporates several features and communication, information, monitoring and controlling tools used for management and coordination of distributed systems of online courses. The key factors of the project are discussed at the end of the paper